2010
DOI: 10.5194/acp-10-2413-2010
|View full text |Cite
|
Sign up to set email alerts
|

Formaldehyde and its relation to CO, PAN, and SO<sub>2</sub> in the Houston-Galveston airshed

Abstract: Abstract. The Houston-Galveston Airshed (HGA) is one of the major metropolitan areas in the US that is classified as a nonattainment area of federal ozone standards. Formaldehyde (HCHO) is a key species in understanding ozone related air pollution; some of the highest HCHO concentrations in North America have been reported for the HGA. We report on HCHO measurements in the HGA from summer 2006. Among several sites, maximum HCHO mixing ratios were observed in the Houston Ship Channel (HSC), a region with a very… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
61
6

Year Published

2013
2013
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 66 publications
(73 citation statements)
references
References 36 publications
6
61
6
Order By: Relevance
“…However, previous studies [55,56] have reported high HCHO levels at noon and low HCHO levels in the morning from the Houston-Galveston Airshed (HGA) and Southern China, which are opposite to the diurnal pattern found in Seoul in this study. As discussed in [52], the different diurnal variations of HCHO seen among various urban areas might be related to differences in the HCHO sources and loss mechanisms at each site.…”
Section: Hcho Vcd Retrieval In Seoul Using Pandoracontrasting
confidence: 55%
“…However, previous studies [55,56] have reported high HCHO levels at noon and low HCHO levels in the morning from the Houston-Galveston Airshed (HGA) and Southern China, which are opposite to the diurnal pattern found in Seoul in this study. As discussed in [52], the different diurnal variations of HCHO seen among various urban areas might be related to differences in the HCHO sources and loss mechanisms at each site.…”
Section: Hcho Vcd Retrieval In Seoul Using Pandoracontrasting
confidence: 55%
“…In order to compare the PMF results directly with the CMAQ source apportionment results from this study, sources of PAN need to be studied to determine the sources of HCHO associated with PAN in the PMF analysis. Although it has been demonstrated during several high HCHO events that PAN is associated with SO 2 and thus is likely to have originated from industrial or petrochemical sources [Rappenglück et al, 2010], the PAN-dominated HCHO resolved by PMF in the study of Buzcu Guven and Olaguer [2011] needs further scrutiny because the PMF analysis identified a separate SO 2 related factor, suggesting that PAN is not always related to SO 2 emitted from industrial sources.…”
Section: Comparison With Pmfmentioning
confidence: 99%
“…More recently, Buzcu Guven and applied Positive Matrix Factorization (PMF) on the same dataset used by Rappenglück et al [2010] and found that HCHO associated with motor vehicle, industry and biogenic factors account for 23%, 17%, and 24% of the total HCHO, respectively.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations